Efektivitas Bahan Ajar Kaiwa II Berbasis Project Based Learning - Yuniarsih, Yuniarsih; Ristiawati, Tia; Fitri Asih, Nur Saadah; Fauziyyah, Fitri; Irawan, Vaniya Safitri (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2022)
The development of kaiwa II teaching materials based on project based learning that pays attention to several aspects of communication (sociolinguistics, turn taking, natural communication), collaboration, creativity, critical thinking and cross-cultural understanding is an urgent need. This is due to the lack of students' ability to use some of these aspects of communication, and the lack of textbooks that explain the characteristics of spoken language in Japanese which is full of cultural content in which there is also a context close to the learner so as to improve cross-cultural understanding skills. This is in line with the idea of ​​learning Japanese based on the JF Standard and 21st century skills. Project based learning is a method that can be applied in kaiwa learning, based on the results of Yuniarsih's research in 2004, 2005 which proves that the application of drama in kaiwa learning can improve skills. student communication, as well as supported by several other relevant research. This research is a follow-up study on the analysis of the needs for Kaiwa II teaching materials which was carried out in 2019 and a feasibility test in 2021. In this 2022 study, an experiment was conducted on the application of textbooks as a product of previous research. This textbook has been validated by experts in Japanese linguistics and language education. The experimental results in quantitative research on 23 students taking Kaiwa II courses, it is known that the application of textbooks in Kaiwa II learning can improve communication skills. Thus, this textbook is effective in learning Kaiwa II and can be used as a reference as a textbook.